Mine geological hazard multi-dimensional spatial data warehouse construction research - Min Ji; Fengxiang Jin; Xiangwei Zhao; Bo Ai; Ting Li (2010 18th International Conference on Geoinformatics, 2010)
Spatial data warehouse has the ability of integrating the mining geological hazard data, and gives the support of complex data analyzing and high-level decision-making. In order to construct such a mining geological hazard multi-dimensional data warehouse, based on the introduction of several concepts of data warehouse, the paper proposed the formal definitions of the dimension, the dimension hierarchy, the mining multidimensional data model and so on. Taking the landslide displacement theme as an example, the paper also identified the dimensions, the dimension hierarchies. Considering the complexity of geological hazard data analyzing, the paper adopted the mixture model to design the mining geological hazard multi-dimensional data warehouse.